Review of the book Americanah by Chimamanda Ngozi Adichie - Krishnamurthy, Sarala (NUST, Department of Communication, 2013)
This article reviews the book entitled: "Americanah" written by Chimamanda Ngozi Adichie, 2013, published by Harper Collins.
Book review
Keywords: Book review; Americanah by Chimamanda Ngozi Adichie